The Influence of Comic Media in Learning Dudaya Arts for Students at SMA Negeri 1 Soromandi - Supryanto, Try; yani, muhammad (Jurnal Ilmiah Mandala Education (JIME), 2024)
This research is experimental research, with the aim of designing comic arts and culture media, knowing the influence of comic media in learning arts and culture among students at SMA Negeri 1 Soromandi and students' responses to comic media. The population in this study was class X students of SMA Negeri 1 Soromandi for the 2024/2025 academic year and the research sample was class Samples were taken using purposive sampling technique. Data on students' concept mastery was obtained using a concept mastery test and student response data was collected using a questionnaire. Student concept mastery data was analyzed using the t-test and student response data was analyzed using five scale absolute norms. In this research, 3 series of Arts and Culture comics have been produced. The results of the analysis show that there is a difference in learning arts and culture through comic media for experimental class and control class students at a significance level of 5% with a value of t'= 3.026 and this value is not in the interval - 2.02, <t' <2.02. This means that comic media in arts and culture learning has an influence on improving the learning of class X students at SMA Negeri 1 Soromandi. while the analysis and questionnaire showed that students responded positively to learning arts and culture using comic media with a percentage of 53.84%